ANALISIS PENGARUH PERSEPSI HARGA, PROMOSI, DESAIN PRODUK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MATIC (Studi Pada Yamaha Mataram Sakti Semarang) - Pahlevi, Anzaruddin Septian; Sutopo, Sutopo (Diponegoro Journal of Management, 2017)
The background of the research is the increasing number of matic motorcycle in Indonesia with the own unique features and characteristic. This phenomeon is related to incresing  demand  of  practical  vehicle  that  can  cater’s  needs  of  high  mobility.  This research aims to analyze price perception (X1), promotion (X2), product design (X3), and product qualit (X4) upon purchasing decision (Y) of matic motorcycle in Yamaha Mataram Sakti Semarang.Population used in this research is consumer bought used mtorcycle in Yamaha Mataram  Sakti  Motor  Semarang.  Total  sample  used  is 100  respondents.  Sampling tehcnique used on this research is purposive sampling. Data used is gathered questionaire, analysis used in this research is multiple regression.The result is, Y = 0,202X1  + 0,212X2  + 0,245X3 + 0,368X4. Independent variable which  is  very  influential  concerning  to dependent  variable is  quality  product  (0,368) followed by product design variable (0,245), promotion (0,212),   and the last is price perception   variable (0,202). The result prove that all of independent variables (price perception, promotion, product design, product quality) have positive influence toward dependent variables that is purchasing decision.